Oncocytic cell carcinoma of the thyroid with TERT promoter mutation presenting as asphyxia in an elderly: a case report - Wang, Xiqian; Liu, Yingao; Chen, Lijie; Zhang, Jie; Jiang, Ruoyu; Zhang, Lei; Yan, Han; Zhang, Jie (Frontiers in Endocrinology, 2024)
Introduction The prevalence of thyroid nodules and malignancies in the elderly is a growing concern. Thyroid nodules in this population have unique characteristics, requiring careful treatment strategies that balance risks and benefits. Oncocytic carcinoma of the thyroid (OCA) is a rare, aggressive subtype with diagnostic challenges. Methods This case features an 84-year-old patient who presented with a neck mass and symptoms of asphyxia. Clinical evaluation, imaging studies, and biopsy were conducted to assess the nature of the thyroid lesion. Molecular testing, including genetic analysis, was performed to identify specific mutations associated with OCA and guide treatment decisions. Results The patient was diagnosed with oncocytic carcinoma of the thyroid. The molecular testing revealed specific genetic mutations indicative of OCA, confirming the diagnosis. The presence of these mutations guided the treatment plan, emphasizing the importance of molecular diagnostics in managing thyroid malignancies, especially in the elderly. Discussion This case illustrates the complexities of diagnosing and treating thyroid malignancies in the elderly. Biopsy and molecular testing provided diagnostic accuracy and informed treatment. Individualized approaches are essential for better outcomes, especially in aggressive subtypes, balancing the risks and benefits of intervention.